Association between the ICAM-1 gene polymorphism and coronary heart disease risk: a meta-analysis. Issue 2 (22nd February 2019) - Yin, De-lu; Zhao, Xin-hua; Zhou, Yi; Wang, Ying; Duan, Ping; Li, Qun-xing; Xiong, Zheng; Zhang, Yang-yang; Chen, Yu; He, Hong; Yang, Kai; Song, He-jian
Abstract : Coronary heart disease (CHD) is a complex polygenic disease in which gene-environment interactions play a critical role in disease onset and progression. The Intercellular adhesion molecule 1 ( ICAM-1 ) gene E469K polymorphism is one of the most commonly studied polymorphisms in this gene because of its association with CHD risks, but results were conflicting. The PubMed, Embase, and China National Knowledge Infrastructure databases were searched for case–control studies published up to November 2018. Pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated to assess the association. Eleven eligible studies, comprising 3435 cases and 3199 controls, were included in the meta-analysis. The pooled result showed that the ICAM-1 gene E469K polymorphism was significantly associated with an increased risk of CHD (OR = 1.20, 95% CI = 1.11–1.29, for the allele K versus allele E; OR = 1.66, 95% CI = 1.43–1.92, for the K allele carriers versus EE). Subgroup analysis supported the results in the Chinese populations and in the Caucasian populations. This meta-analysis suggests that the ICAM-1 gene K469E polymorphism is associated with CHD risk and the K allele is a more significant risk factor for developing CHD amongst Chinese and Caucasians populations.